2017
DOI: 10.1080/00343404.2017.1331296
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, heterogeneous firms and the region: evidence from Spain

Abstract: This paper investigates the role of regional factors in innovation performance, controlling for firms' absorptive capacity and other sources of firm heterogeneity. The findings for a sample of firms in Spain support the hypothesis that regional determinants matter, though their role is subtler than is frequently assumed. Rather than exerting a direct influence on firms' innovation, the regional context moderates the effect of internal determinants, particularly of the firms' absorptive capacity. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
4
22
1
1
Order By: Relevance
“…Nevertheless, it is highly idiosyncratic at the company level and not freely and automatically disseminated among companies but rather absorbed by firms based on their accumulated capabilities. López-Bazo and Motellón (2017) found that the regional context moderates the effect of internal determinants-particularly, firms' absorptive capacity-and showed that the relevant interactions operate only for small and mediumsized enterprises and are negligible for large firms.…”
Section: Systems Of Innovationmentioning
confidence: 99%
“…Nevertheless, it is highly idiosyncratic at the company level and not freely and automatically disseminated among companies but rather absorbed by firms based on their accumulated capabilities. López-Bazo and Motellón (2017) found that the regional context moderates the effect of internal determinants-particularly, firms' absorptive capacity-and showed that the relevant interactions operate only for small and mediumsized enterprises and are negligible for large firms.…”
Section: Systems Of Innovationmentioning
confidence: 99%
“…At the same time, expanding a firm's absorptive capacity through R&D investment provides it with greater opportunity to connect with global pipelines of new technologies, moving beyond a reliance on local networks (Bathelt et al, 2004;Trippl et al, 2018). However, there is also evidence that R&D investment enhances a firm's ability to capture and exploit knowledge generated locally (Lo´pez-Bazo and Motello´n, 2018;Prenzel et al, 2018).…”
Section: Localised Knowledge Spillovers and Randd Spendmentioning
confidence: 99%
“…In Spain, as local authorities have increasingly assumed competences, the total number of new regulations in a given year has increased by four folds since 1980, with the share of those introduced by local authorities reaching over 70% in 2018 (Mora-Sanguinetti and Pérez-Valls, 2020 [56]). Moreover, firms perceive an increase in regulations to operate in different regions as of 2019 (INE, 2020 [57]). The disparities in regulation across regions hamper the expansion of firms to take advantage of economies of scale.…”
Section: Market Regulation Should Be Revamped Further To Generate Competitive Pressuresmentioning
confidence: 99%